대학 인문교양교육에 대한 만족도 및 수업효과에 대한 인식 분석 – A 대학을 중심으로 - 김무영; 김민영 (교양교육연구, 14(1), 2020)
이 연구에서는 A대학의 인문교양 교육과정에 대한 인문교양교육의 중요성, 전반적인 만족도, 교육과정, 교수학습 및 평가방법, 수업효과 등에 대한 학생들의 인식과 인문교양교육에 대한 만족도와 만족도에 영향을 미치는 요인들 간의 관계를 분석하여 인문교양교육의 개선을 위한 시사점을 을 제시하는 것을 목적으로 한다. 분석 결과, 대다수의 대학생들이 인문학적 소양을 형성하는 것에 대해 긍정적으로 생각하고 있고, 인문학이 제시하는 가치들이 현 시대에 있어 중요하다고 생각하고 있으며, 또한 협업 역량과 의사소통 역량이 향상되었다고 응답하였다. 반면 인문학 수업을 수강할 의사와 학점 이수의 필수성에 대해서는 타 질문에 비해 다소 부정적인 대답이 높게 나타났다. 다음으로 인문교양 교육과정과정과 교수 학습 및 평가 방법에 대한 인식을 묻는 설문 결과, 대학의 인문학 강의의 내용이나 수준은 긍정적인 응답을 많이 한 것으로 나타났으며, 인문교양 교과 담당교원에 있어서는 비교적 긍정적인 응답들이 많이 나타났으나, 동기부여, 수업방식, 상호작용에 있어 부정적 의견이 상대적으로 높아 관련 교과 담당교원들이 보완할 필요성이 있는 것으로 나타났다. 다음으로 인문교양 교과 참여자의 수업효과에 대한 인식을 묻는 설문 결과, 수업을 통해 인문학 관련 개념이나 지식의 형성, 사회 현상과 공동체의 소중함에 대한 관심, 창의성과 합리적인 의사결정이 대해서 긍정적인 응답이 나타났다. 마지막으로, 인문교양 교육과정 만족도 및 관련 요인들과의 관계에 대해서는 인문교양교육과정 전반에 대한 만족도에 대해 인문교양 교육과정 편성 및 강좌 구성이 좋을수록, 교수학습 및 평가방법이 좋을수록 개인 능력 신장에 도움이 될수록 만족도가 높아지는 것으로 나타났다. 이와 같은 결과를 토대로 인문교양교육과정 운영 개선에 대해 몇 가지 점들을 고려해 볼 수 있다. 첫째, 인문교양교육을 강화할 수 있는 교과목 및 프로그램을 개발할 필요성이 있다. 둘째, 학생들의 관심과 흥미를 유발할 수 있는 인문교양 교육방법론의 개발이 시급하다고 할 수 있다. 셋째, 취업이라는 직면하고 상황에의 도움보다 미래사회에 필요한 자아 성찰, 사회적 협력과 이를 통해 문제들을 해결하는 능력 등을 가진 인재가 되기 위해서는 인문교양교육이 그 밑거름이 될 것이라는 인식을 심어 줄 필요가 있다. This study aims to analyze students’ perception, satisfaction, course of liberal education of humanities, teaching-learning and assessment methods and learning outcomes of liberal education of humanities and to propose the developmental direction of a liberal education of humanities in A university curriculum. The results of this study are as follow. First, the majority of students responded positively to shaping the humanities, thinking that the values offered by the humanities were important in the current era, and that their collaboration and communication skills improved. On the other hand, the negative response was higher than the other questions about the thought of taking a humanities lecture and the necessity of credit. Second, as a result of the questionnaire asking about recognition of the humanities and liberal arts curriculum and the methods of teaching and learning, the contents and level of the university's humanities lectures showed a lot of positive responses. However, the negative opinions on motivation, teaching method, and interaction are relatively high, and the related subjects need to be supplemented. Third, as a result of the questionnaire about learning outcomes of participants in the liberal arts lecture, the class showed positive responses to the formation of humanities related concepts or knowledge, interest in social phenomena and community importance, creativity and rational decision making. Lastly, as for the satisfaction of the liberal arts curriculum and the relations with the related factors, the better the composition and course composition of the liberal arts curriculum for the satisfaction of the general liberal arts curriculum, and the better the teaching and learning methods, the greater the individual ability. The more they helped, the higher their satisfaction. Based on the findings, the educational implications to improve liberal education of humanities were suggested. First, there is a need to develop curricula and programs that can enhance humanities education. Second, it is urgent to develop teaching methods for humanities that can induce students' interest and interest. Third, it is necessary to raise awareness that liberal arts education will be the foundation for being a talented person who is faced with employment and needs self-reflection, social cooperation and ability to solve problems through future situation rather than help in the situation. KCI Citation Count: 5